Comparison of stapled haemorrhoidopexy with traditional excisional surgery for haemorrhoidal disease (eTHoS): a pragmatic, multicentre, randomised controlled trial. Issue 10058 (12th November 2016) - Watson, Angus J M; Hudson, Jemma; Wood, Jessica; Kilonzo, Mary; Brown, Steven R; McDonald, Alison; Norrie, John; Bruhn, Hanne; Cook, Jonathan A; ,
Summary: Background: Two commonly performed surgical interventions are available for severe (grade II–IV) haemorrhoids; traditional excisional surgery and stapled haemorrhoidopexy. Uncertainty exists as to which is most effective. The eTHoS trial was designed to establish the clinical effectiveness and cost-effectiveness of stapled haemorrhoidopexy compared with traditional excisional surgery. Methods: The eTHoS trial was a large, open-label, multicentre, parallel-group, pragmatic randomised controlled trial done in adult participants (aged 18 years or older) referred to hospital for surgical treatment for grade II–IV haemorrhoids. Participants were randomly assigned (1:1) to receive either traditional excisional surgery or stapled haemorrhoidopexy. Randomisation was minimised according to baseline EuroQol 5 dimensions 3 level score (EQ-5D-3L), haemorrhoid grade, sex, and centre with an automated system to stapled haemorrhoidopexy or traditional excisional surgery. The primary outcome was area under the quality of life curve (AUC) measured with the EQ-5D-3L descriptive system over 24 months, assessed according to the randomised groups. The primary outcome measure was analysed using linear regression with adjustment for the minimisation variables. This trial is registered with the ISRCTN registry, number ISRCTN80061723. Findings: Between Jan 13, 2011, and Aug 1, 2014, 777 patients were randomised (389 to receive stapled haemorrhoidopexy and 388 to receive traditional excisional surgery). Stapled haemorrhoidopexy was less painful than traditional excisional surgery in the short term and surgical complication rates were similar between groups. The EQ-5D-3L AUC score was higher in the traditional excisional surgery group than the stapled haemorrhoidopexy group over 24 months; mean difference −0·073 (95% CI −0·140 to −0·006; p=0·0342). EQ-5D-3L was higher for stapled haemorrhoidopexy in the first 6 weeks after surgery, the traditional excisional surgery group had significantly better quality of life scores than the stapled haemorrhoidopexy group. 24 (7%) of 338 participants who received stapled haemorrhoidopexy and 33 (9%) of 352 participants who received traditional excisional surgery had serious adverse events. Interpretation: As part of a tailored management plan for haemorrhoids, traditional excisional surgery should be considered over stapled haemorrhoidopexy as the surgical treatment of choice. Funding: National Institute for Health Research Health Technology Assessment programme.